Distributed control and filtering for industrial systems - Mahmoud, Magdi S. (IET control engineering series, 2013)
Distributed Control and Filtering for Industrial Systems provides an introduction to the control and filtering algorithms devised for distributed environments, with a particular emphasis on industrial applications.